Pengaruh Kompensasi, Kepuasan Kerja dan Pengembangan Karir terhadap Kinerja Pegawai Dinas Pekerjaan Umum Kabupaten Teluk Wondama - Sawakii, Alexx; Made Yudhi Setiani; Askar Taliang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Employees of the Public Works Department of Teluk Wondama Regency feel that they have given good performance, but the provision of additional employee income compensation (TPP) cannot provide job satisfaction because some employees are actively working and inactive or lazy, the additional income payment is paid the same amount. This makes active employees feel dissatisfied with the performance they have done. In addition, in uneven career development and more than half of the employees are high school education which has an impact on their abilities and skills in carrying out their performance. The purpose of this study was to determine partially and simultaneously the effect of compensation, job satisfaction and career development on the performance of employees of the Public Works Department of Teluk Wondama Regency. The research method is associative to determine the relationship between the two (or more) variables. The population is civil servants with a sample size of 91 people. Data were obtained using a questionnaire and analyzed using multiple regression. The results of the study showed that compensation has a positive and significant effect on employee performance at the Public Works Department of Teluk Wondama Regency (t count = 2.470> t table = 1.662557 and significance 0.015 <0.05. Job satisfaction has a positive and significant effect on employee performance at the Public Works Department of Teluk Wondama Regency (t count = 11.712> t table = 1.662557 and significance 0.000 <0.05). Career development has a positive and significant effect on employee performance at the Public Works Department of Teluk Wondama Regency (t count = 3.686> t table = 1.662557 and significance 0.000 <0.05. There is a significant simultaneous effect between compensation (X1), job satisfaction (X2), career development (X3) on employee performance (Y) at the Public Works Department of Teluk Wondama Regency ((f count = (247.308) > (2.689490) with a contribution of 96.5% and 3.5% explained from outside variables in this study. Keywords: Compensation, Job Satisfaction, Career Development, Performance